2008
DOI: 10.1519/jsc.0b013e3181875117
|View full text |Cite
|
Sign up to set email alerts
|

Jaw Clenching Results in Concurrent Activation Potentiation During the Countermovement Jump

Abstract: The study assessed the effect of current activation potentiation by evaluating jaw clenching and its effect on the rate of force development (RFD), time to peak force (TTPF), and peak force (PF) during the countermovement jump. Fourteen subjects performed the countermovement jump on a force platform while maximally clenching their jaw on a dental vinyl mouthguard (JAW) as well as without clenching their jaw by jumping with an open mouth (NON-JAW). Results reveal that the RFD was 19.5% greater in the JAW compar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
82
2
4

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 63 publications
(92 citation statements)
references
References 18 publications
4
82
2
4
Order By: Relevance
“…It is suggested that these motor activities contribute to the facilitation of human motor system excitability [5,6,12], which increases the neural drive to the distal muscles [13,14] in a manner similar to the Jendrassik manoeuvre [15].…”
Section: Discussionmentioning
confidence: 99%
“…It is suggested that these motor activities contribute to the facilitation of human motor system excitability [5,6,12], which increases the neural drive to the distal muscles [13,14] in a manner similar to the Jendrassik manoeuvre [15].…”
Section: Discussionmentioning
confidence: 99%
“…Procedures Th e experimental model of the CAP modifi ed swimming start has been elaborated upon based on the outcomes of previous studies [3][4][5], and taking into account our experience in start technique investigation in Olympic swimmers [9]. Th e technique protocol included teeth clenching and voluntary contraction of abdominal muscles, which were initiated immediately aft er the preliminary starting command ("take your marks").…”
Section: Subjectsmentioning
confidence: 99%
“…Furthermore, a number of studies evaluated the potentiation eff ect of RVC combined with the performance of various speed-strength exercises, termed Concurrent Activation Potentiation (CAP) [2]. Th us, a signifi cant ergogenic eff ect of CAP has been found during the performance of the high jump, squat jump, back squat, and knee fl exion and extension [3][4][5]. Th ese publications reported gains of maximal force, rate force development, and jump height that varied within 4.2-32.2% depending on the character of the variables and experimental conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Des études montrent que le port d'un protège-dents de performance permet d'augmenter le PP mais aussi de l'atteindre plus rapidement et de le maintenir plus longtemps [9,17,18]. Cependant des résultats contraires ont également été publiés [19,20]. Les différences de résultats obtenus entre les études en termes d'amélioration de la résistance chez les porteurs de protège-dents soulignent l'inhomogénéité de ces études notamment parce qu'elles portent sur des exercices physiques très différents.…”
Section: Fig 3 Different Types Of Under Armour Performance Mouthweaunclassified
“…Plusieurs études ont confirmé l'effet neuromusculaire de l'activité motrice orale et des différentes positions de la mandibule sur le contrôle postural [50]. Des études suggèrent que l'augmentation de la force musculaire lors du serrement des dents serait la consé-quence du concurrent activation potentiation ou en français la « potentialisation par activation simultanée » qui optimiserait la commande descendante [18,19,51]. Le principe de cette potentialisation est que la force d'un muscle A devient plus importante si les muscles B (les muscles masticateurs par exemple) sont contractés en même temps.…”
Section: Approche Neuromusculaireunclassified